Fibrinolysis Shutdown in Trauma: Historical Review and Clinical Implications - Moore, Hunter B. (Anesth Analg, 2019)
Despite over a half-century of recognizing fibrinolytic abnormalities after trauma, we remain in our infancy in understanding the underlying mechanisms causing these changes, resulting in ineffective treatment strategies. With the increased utilization of viscoelastic hemostatic assays (VHAs) to measure fibrinolysis in trauma, more questions than answers are emerging. Although it seems certain that low fibrinolytic activity measured by VHA is common after injury and associated with increased mortality, we now recognize subphenotypes within this population and that specific cohorts arise depending on the specific time from injury when samples are collected. Future studies should focus on these subtleties and distinctions, as hypofibrinolysis, acute shutdown, and persistent shutdown appear to represent distinct, unique clinical phenotypes, with different pathophysiology, and warranting different treatment strategies.